Rancang Bangun Aplikasi Subnetting Berbasis Web dengan AI Assistant untuk Otomatisasi Perhitungan Pengalamatan Jaringan IPv4 - Nelani Shafatia Zulatifa; Nisa Dwi Septiyanti (Bulletin of Computer Science Research, 2025)
Subnetting is a fundamental concept in computer networking that is often considered difficult due to its complex calculation process and the limited availability of interactive learning media. This study developed SubnetLab, a web-based learning application that provides user authentication features, an automatic subnetting calculator, binary representation, and a reset function to support independent exploration of the concept. The study used a Research and Development (R&D) method through the stages of needs analysis, design, implementation, and functional testing. The application was built using HTML, CSS, and JavaScript with account storage on localStorage. The results showed that SubnetLab was able to perform subnetting calculations accurately and display results in decimal and binary formats. All main features functioned well and supported usability aspects in the basic usage scheme. However, this study did not evaluate the effectiveness of learning or increase user understanding, so further studies are needed to assess the pedagogical impact of the application more comprehensively. Based on these findings, SubnetLab has the potential to be further developed as an independent learning medium or as a companion for computer networking practicums.